2003
DOI: 10.1086/502179
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Approach to Percutaneous Injury Prevention During Phlebotomy: Results of a Multicenter Study, 1993-1995

Abstract: Device-specific features and healthcare worker training and involvement in the selection of ESIPDs affect the activation rates for ESIPDs and therefore their efficacy. The implementation of ESIPDs is a useful measure in a comprehensive program to reduce percutaneous injuries associated with phlebotomy procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 6 publications
(7 reference statements)
1
38
1
1
Order By: Relevance
“…Workload pressures and time constraints are likely to cause both needle-stick injuries 10,11 and underreporting. Our survey does not indicate whether the advent of safer needle devices, [12][13][14] has lessened the risk of injury. Initial studies indicate these devices to be cost-effective, and introduction in some hospitals in the United States has become compulsory.…”
Section: Discussionmentioning
confidence: 93%
“…Workload pressures and time constraints are likely to cause both needle-stick injuries 10,11 and underreporting. Our survey does not indicate whether the advent of safer needle devices, [12][13][14] has lessened the risk of injury. Initial studies indicate these devices to be cost-effective, and introduction in some hospitals in the United States has become compulsory.…”
Section: Discussionmentioning
confidence: 93%
“…40 Using an extensive hands-on training program and implementation of the device throughout the facility, the authors demonstrated an approximate twofold reduction in the injury rate with such devices. Although the effect of this engineered sharps injury protective device on injuries did not reach significance in the prior, larger study, 39 Mendelson et al demonstrated an effect in their large referral hospital. 40 Importantly, this effect was maintained during a 31-month follow-up period.…”
Section: Lessons Regarding Percutaneous Injuries Amongmentioning
confidence: 78%
“…37,38 Two articles in this issue provide further convincing evidence of die role of engineered sharps injury protective devices, when incorporated as part of a comprehensive program to protect healthcare workers. 39,40 However, as these studies and other research show, adequate training must be provided in the appropriate use of these devices. Even when "safer" sharps devices are made available and used, they are often not adequately activated.…”
Section: Lessons Regarding Percutaneous Injuries Amongmentioning
confidence: 98%
See 1 more Smart Citation
“…El uso de dispositivos médicos de bioseguridad aumenta la seguridad de los trabajadores sanitarios 41 , pero debe ser considerado como un componente de un programa más extenso para prevenir la transmisión ocupacional de VIH en el medio sanitario. El conjunto de todas las medidas de control administrativas y de ingeniería es, junto con el uso de equipos de protección individual y prácticas de trabajo más seguras, la manera más efectiva de prevenir la exposición ocupacional al VIH.…”
Section: Tablaunclassified